Feasibility Study of Adopting Minimal Quantities of Lubrication for End Milling Aluminium - Boswell, Brian; Islam, Mohammad Nazrul (Newswood Limited, International Association of Engineers, 2012)
End milling is a very common metal cutting process used for the machining of most types of metal. The process is inherently intermittent causing the tool tip edge to constantly fluctuate between various levels of temperatures, specifically from cold to 300oC when cutting Al alloy. During dry end milling cutting temperatures need to remain within the design specifications of the tool tip. Even working with Al alloy the tool tip is subjected to thermal cyclic stresses. Conventional wisdom states that it is essential to use flood cooling during end milling, as intermittent cooling increases the effect of thermal shock and build up edge. Al alloy - unlike other materials - needs cutting fluid to avoid smearing the insert edges and to improve the surface finish. Modern machining companies constantly face the challenges of environmental issues that affect the manufacturing costs of machined parts. New environmental manufacturing techniques need to be developed for companies to remain competitive in the future. The research presented in this paper represents the experimentation involved in determining a suitable environmental alternative to using copious amounts of cutting fluid during end milling of Al alloy. Previous experimental evaluation of Minimal Quantities of Lubrication (MQL) when applied to the machining of Al alloy has proved to be inconclusive.